Uji Aktivitas Antibakteri 1-[(Kuinazolin-4-on-2-il)metil]piridin-1-ium Bromida dan 2-Bromometilkuinazolin-4-on - Hayun, Hayun; Arrahman, Arif; Suryadi, Herman; Yanuar, Arry (UI Scholars Hub, 2014)
Antibacterial activity tests of quinazolin-4-one derivates: 1-[(6-nitroquinazolin-4one-2-yl)methyl]piridin-1-ium bromide (1), 1-[(6-aminoquinazolin-4-on-2-yl)methyl] piridin-1-um bromide (2), 2-bromomethylquinazolin-4-one (3) and 2-bromomethyl-6nitroquinazolin-4-one(4) with trimethoprim (5) as a positive standard were conducted. The antibacterial activity tests were carried out using disc diffusion method againts E.coli, S.aureus and S.thyposa, and determination of minimum inhibitory concentration (MIC). The results showed that compounds 1 and 2 are inactive as antibacterial, whereas compounds 3 and 4 are active.The activities to E.coli were ¼ times the activity of trimethoprim (MIC : 5 x 102 µg/ml compared to 1.25 x 102 µg/ml ). The activity to S. typhosa were ½-1 times the activity of trimethoprim (MIC: 2.5 and 1.25x102 µg/ml compared to 1.25x102 µg/ml); but they are not active to S. aureus. Trimethoprim active to S. aureus with MIC : 0.62 x102 µg/ ml.